Externally initiated event in sequential risk assessment for the onshore LNG marine loading arm unit - Dirik, Cengiz; Awang Biak, Dayang Radiah; Abdul Razak, Mus'ab; Nik Ibrahim, Nik Nor Liyana (Elsevier, 2022)
This paper describes the failure assessment of the unloading arm unit that is connected to a Liquified Natural Gas (LNG) terminal. In this work, an external event, i.e., lightning, was simulated as the triggering event. A Temporal Fault Tree (TFT) analysis was developed, and sequential failures that function under the Priority AND (PAND) gate were assessed. The results show that the highest contributing factor to the failure of the terminal unloading arm was the sequential failure due to the loss of sensors which can happen before or after lightning strikes. The occurrence of failures for the loading arm was estimated using a Monte Carlo Simulation (MCS). For service years of 32.7, the sequential failures occurred 131 times when preventive maintenance was not considered. This work also presents that the failure distribution of the marine loading arm follows the Weibull distribution characteristic with the scale (α) and the shape (β) parameters values of 132,817.5 h-1 and 1.556, respectively.